Caregiver burden: Support needed for those who support others and the National Health Service - Michael Stephanou (The Beryl Institute, 2023)
This literature review focuses on the complexities and inequalities of informal caregiving in the UK and was inspired by the story of the following individual: EL is a 68-year-old Caucasian lady who attended Movement Disorder Clinic and was diagnosed with Parkinson's Disease Dementia following many years of symptoms. The diagnosis came as a big relief to EL and her daughter (SL) who were eager to get treatment started as soon as possible. EL lives alone with SL and solely relies on her for care and support. SL does not have children and devotes her daily routine to looking after her mother, never spending more than a few hours away from her. SL has found this situation very challenging, while EL has felt she has lost her independence. This frustration on a background of mutual love and concern was evident from both parties during the appointment. Informal carers play a crucial role in looking after individuals and provide massive relief to healthcare systems but are often left without support. This puts themselves and the people they care for at risk of poor physical and psychological outcomes. The number of informal carers continues to rise but staggering rates of burnout are still observed. By understanding the complexities and emotional impact of this role, together with the inadequacies of current social care policies, we can strive to reveal areas of improvement that can grant carers the support they deserve to carry on performing their invaluable roles. Experience Framework This article is associated with the Staff & Provider Engagement lens of The Beryl Institute Experience Framework (https://theberylinstitute.org/experience-framework/). Access other PXJ articles related to this lens. Access other resources related to this lens.